Caricatures and comics based on gender towards concept understanding: A learning media on environmental pollution - Sisean Baga; Deden Ibnu Aqil; Maria Magdalena Rosaline (Biosfer: Jurnal Pendidikan Biologi, 2022)
One crucial thing in environmental learning is how gender-based media is not yet used optimally to improve concept understanding in the classroom. Students will not develop pro-environmental concerns and behavior if they do not understand pollution and environmental issue. This study aims to prove the influence of learning media and gender on understanding environmental pollution concepts in a Secondary High School in Jakarta, Indonesia. The method used is an experiment with a 2 x 2 factorial design. The sample is taken based on the stratified random sampling technique that consists of 40 students with 20 males and 20 females from two Senior High Schools in Jakarta, Indonesia. The instrument used in this study was 32 multiple choice questions to measure students' understanding, consisting of translating, interpreting, and extrapolating dimensions. The data analysis interpretation shows an interaction effect between learning media and gender on understanding the environmental pollution concept. Therefore, this study recommends that teachers use various media such as caricatures and comics that are proven usable to accommodate gender differences and enhance conceptual understanding in the classroom.